1997
DOI: 10.1016/s1074-7613(00)80330-1
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-A*0201-Restricted H-Y Antigen Contains a Posttranslationally Modified Cysteine That Significantly Affects T Cell Recognition

Abstract: A peptide recognized by two cytotoxic T cell clones specific for the human minor histocompatibility antigen H-Y and restricted by HLA-A*0201 was identified. This peptide originates from SMCY, as do two other H-Y epitopes, supporting the importance of this protein as a major source of H-Y determinants in mice and humans. In naturally processed peptides, T cells only recognize posttranslationally altered forms of this peptide that have undergone modification of a cysteine residue in the seventh position. One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
163
2
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(169 citation statements)
references
References 39 publications
2
163
2
2
Order By: Relevance
“…Here through studies of a cysteine-containing peptide from the Ag human Ig , we have demonstrated that cysteine modification can regulate T cell responses to class II-restricted epitopes. Although cysteinylation of ligands for MHC class I has been reported previously (35)(36)(37), this marks the first demonstration that such a modification can alter class II-restricted T cell responses. Furthermore, these studies demonstrate that endocytosis and processing of the cysteinylated peptide by viable APC was necessary to restore antigenicity.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Here through studies of a cysteine-containing peptide from the Ag human Ig , we have demonstrated that cysteine modification can regulate T cell responses to class II-restricted epitopes. Although cysteinylation of ligands for MHC class I has been reported previously (35)(36)(37), this marks the first demonstration that such a modification can alter class II-restricted T cell responses. Furthermore, these studies demonstrate that endocytosis and processing of the cysteinylated peptide by viable APC was necessary to restore antigenicity.…”
supporting
confidence: 51%
“…Although dimerization and oxidation of these cysteine-containing peptides was detected, by far the most common modification was peptide cysteinylation. In vivo cysteinylation of peptides is highly likely due to the high circulating levels of cystine in serum (0.1 mM) and the reactivity of free sulfhydryls (36,62). The importance of cysteinylation in regulating class II-restricted T cell activation, has not been investigated despite elegant studies pointing to the role of disulfide reduction and cysteine residues in Ag unfolding, processing, and class II presentation (29,30,39,42,63,64).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If conversion of tyrosine to nitrotyrosine in autologous proteins can render these proteins recognizable as immunogenic autoantigens, this could have important implications for autoimmune diseases. Recent studies have indicated that a host of post-translational modifications, including glycosylation (19,20), phosphorylation (21,22), and cysteinylation (23,24), can all affect T cell immunoreactivity. Indeed, it has been proposed that these modifications may play a role in the initiation and/or maintenance of autoimmune disease by contributing to the breakdown of immunological tolerance (25,26).…”
mentioning
confidence: 99%